Exploring Transformational Leadership Skills in Senior Management Across Pakistan, UAE, and the USA - Haq, Nabeel K. (Digital Repository of Theses, 2026)
Findings reveal that while transformational leadership principles are universally valued, their manifestation is deeply shaped by cultural norms, economic structures, and organizational dynamics. In Pakistan, leadership tends to blend traditional hierarchical values with modern participative practices, creating hybrid models that balance authority with empowerment. The UAE demonstrates a multicultural leadership landscape where cultural intelligence and inclusivity are essential for managing diverse teams. In contrast, the USA emphasizes autonomy, innovation, and employee empowerment, aligning with its low power-distance and individualistic culture. Four overarching themes emerged from the data: Structured Leadership in Dynamic Cultures, Leading with Integrity and Trust, Empowering Employees for Innovation and Growth, and Culture of Human-Centered Leadership. Across all contexts, transformational leaders were found to enhance organizational performance by fostering trust, promoting learning, and aligning individual aspirations with collective goals. The study contributes to cross-cultural leadership theory by developing a conceptual framework that integrates transformational leadership with cultural adaptability. It provides actionable insights for multinational organizations, policymakers, and educational institutions to design culturally responsive leadership development programs. Ultimately, the research underscores that effective global leadership requires not only vision and influence but also empathy, cultural awareness, and ethical integrity in navigating diverse organizational landscapes.